2008
DOI: 10.1038/sj.cdd.4402314
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analyses of c-FLIPR, the only murine short FLIP isoform, reveal requirements for DISC recruitment

Abstract: Cellular FLICE-inhibitory protein (c-FLIP) proteins are known as potent inhibitors of death receptor-mediated apoptosis by interfering with caspase-8 activation at the death-inducing signaling complex (DISC). Among the three human isoforms, c-FLIP long , c-FLIP short and c-FLIP R , the latter isoform is poorly characterized. We report here the characterization of murine c-FLIP R and show that it is the only short c-FLIP isoform expressed in mice. By generating several mutants, we demonstrate that both death ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 24 publications
0
69
1
Order By: Relevance
“…The different c-FLIP isoforms are also randomly recruited to the chains via the FL-motif, in a ratio to procaspase-8 of 1-10, which is followed by processing of c-FLIP L to p43-FLIP (Figure 8b). 34,37 Remarkably, our data indicate that the previously suggested mechanism of procaspase-8 inhibition by c-FLIP, based on the competition for binding sites at the DISC, is not valid. Our data indicate that likely c-FLIP S/R has an inhibitory potential, if the DED chain is mostly composed of c-FLIP S/R /procaspase-8 heterodimers, which would prevent procaspase-8 homodimer formation.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The different c-FLIP isoforms are also randomly recruited to the chains via the FL-motif, in a ratio to procaspase-8 of 1-10, which is followed by processing of c-FLIP L to p43-FLIP (Figure 8b). 34,37 Remarkably, our data indicate that the previously suggested mechanism of procaspase-8 inhibition by c-FLIP, based on the competition for binding sites at the DISC, is not valid. Our data indicate that likely c-FLIP S/R has an inhibitory potential, if the DED chain is mostly composed of c-FLIP S/R /procaspase-8 heterodimers, which would prevent procaspase-8 homodimer formation.…”
Section: Discussioncontrasting
confidence: 56%
“…In line with this, it has been reported that the charge triad motif of murine c-FLIP R is not required for its recruitment to the DISC and inhibition of procaspase-8 activation. 37 Chain termination depends on procaspase-8 dissociation/association rates. To strive better understanding of chain termination control, we used mathematical modeling.…”
Section: Resultsmentioning
confidence: 99%
“…At the protein level, c-FLIP has three different isoforms -FLIPl, FLIPr and FLIPs -in humans, and two -FLIPl and FLIPr -in mice. [19][20][21][22][23][24] In this report, we demonstrate that p63 activates the genes of both procaspase-8 and of its negative regulator, c-FLIP.…”
mentioning
confidence: 49%
“…28 Low concentrations of c-FLIP L promote caspase-8 recruitment and activation, whereas high concentrations of c-FLIP L inhibit capase-8 activation, likely due to competition for FADD interaction. 22 Isoforms of c-FLIP lacking its caspase-like domain (c-FLIPs and c-FLIP R , the only short c-FLIP isoform expressed in the mouse, 29 ), as well as viral forms of FLIP act solely as potent inhibitors of caspase-8 recruitment and activation. [29][30][31] The Bcl-2 Protein Family and its Role in the Regulation of Apoptosis…”
Section: The Death Receptor Fasmentioning
confidence: 99%